Enrichment of Porphyromonas gingivalis in colonic mucosa-associated microbiota and its enhanced adhesion to epithelium in colorectal carcinogenesis: Insights from in vivo and clinical studies. - Shunya Motosugi; Naoki Takahashi; Shuhei Mineo; Keisuke Sato; Takahiro Tsuzuno; Yukari Aoki-Nonaka; Nao Nakajima; Kazuya Takahashi; Hiroki Sato; Haruna Miyazawa; Koji Taniguchi; Shuji Terai; et al. (PLoS ONE)
Objectives The oral-gut axis is believed to play a role in the pathogenesis of colorectal cancer (CRC). Previous studies have demonstrated the transmission of oral microbiota to the gut, disrupting gut microbial balance and creating a protumorigenic microenvironment conducive to CRC progression. Fusobacterium nucleatum is a putative periodontal pathogen recognized as a specific bacterium that promotes CRC development. However, the possible involvement of other periodontal pathogens in CRC is poorly understood. This study aimed to explore the effects of ingested periodontal pathogens on experimental CRC in mice and elucidate the underlying mechanisms. Methods In this study, experimental colitis-induced CRC mouse models were used. The mice were orally administered periodontal pathogens (Porphyromonas gingivalis and Prevotella intermedia) three times a week during the experimental period. The CRC severity between the P. gingivalis-treated and P. intermedia-treated groups was compared. Lumen-associated microbiota (LAM) and mucosa-associated microbiota (MAM) were analyzed in both mouse and human samples. In vitro studies were conducted using intestinal epithelial cells to explore the possible mechanisms by which the periodontal pathogens affect the CRC development. Results The P. gingivalis-treated group exhibited significantly increased CRC severity compared to the other groups among azoxymethane/dextran sodium sulfate (AOM/DSS)-induced mouse models. The LAM and MAM exhibited distinct bacterial compositions, and P. gingivalis was enriched more in MAM than in LAM. In vitro adhesion assays revealed that P. gingivalis had higher adhesive capacity to intestinal epithelial cells than P. intermedia and indicated the possible involvement of gingipains in such a capacity. Conclusion P. gingivalis is enriched in MAM, and its subsequent adhesion to intestinal epithelial cells is potentially involved in the progression of CRC.